EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1960)
Abstract The article presents questions and answers for the examination in theory of accounts of the November, 1959, Uniform Certified Public Accountants examination. The first question was related to depreciation of assets and its objectives. The answer to the question is given. Accounting for depreciation is the process of allocating the cost of plant assets of limited life over their estimated useful lives. The chief objective is to charge against each period's revenue its fair share of the depreciable portion of the cost of such assets. This portion is original cost minus any expected scrap or trade-in value. The time period is affected by obsolescence to the extent predictable, by accidents, by repair and maintenance policy, by extent of asset usage, and other factors. Recording port assets at cost less accumulated depreciation on the balance sheet. Decreasing charge methods such as sum-of-year's-digits or fixed per cent on diminishing base are consistent with this objective. Appropriateness of the selection depends on circumstances of asset use.